Grip socks improve slalom course performance and reduce in-shoe foot displacement of the forefoot in male and female sports players - Apps, C.; Dawson, L.; Shering, B.; Siegkas, P. (Journal of Sports Sciences, 2022)
This study assessed whether grip socks reduce in-shoe foot motion and improve change of direction performance in team sports players and compared the effects between males and females. A sledge and pulley system confirmed the static coefficient of friction was increased in the grip socks (1.17) compared to the regular socks (0.60). Performance during a slalom course was faster in the grip socks compared to regular socks (p = .001). Yet, there was no difference in the utilised coefficient of friction between the shoe-floor interface during a side-cut and turn change of direction manoeuvre. Three-dimensional motion capture revealed the grip socks reduced in-shoe foot displacement during the braking phase, with greater effect during the sharper turn manoeuvre. The magnitude of natural foot spreading within the shoe was greater in the calcaneus region than the metatarsals which suggests in-shoe sliding may only occur at the forefoot. Males tended to have increased in-shoe displacement, which is associated with larger foot spreading due to their increased mass. Findings provide guidance for product developers to enhance the support inside the shoe at the forefoot, and change of direction performance.